2020
DOI: 10.1001/jama.2020.5893
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and Addressing Sources of Anxiety Among Health Care Professionals During the COVID-19 Pandemic

Abstract: This Viewpoint discusses sources of anxiety revealed in conversations with health care workers (HCWs) in the early weeks of the coronavirus disease 2019 (COVID-19) pandemic, and the importance of expressions of gratitude from leadership for HCWs’ commitment and willingness to put themselves in harm’s way as a means to ameliorate that anxiety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

68
1,568
3
85

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 1,606 publications
(1,724 citation statements)
references
References 6 publications
68
1,568
3
85
Order By: Relevance
“…Des cellules d'écoute individuelle ont ainsi été mises en place dans de nombreux établissements. Elles ne constituent pas à elles seules cependant, les mesures de prévention primaire visant à limiter à long terme l'impact psychologique de la crise (17,18,36,37). Ces dispositifs se déclinent au niveau de l'institution, de l'encadrement et des soignants, et participent à la reconnaissance du caractère professionnel du stress.…”
Section: Addictionsunclassified
See 1 more Smart Citation
“…Des cellules d'écoute individuelle ont ainsi été mises en place dans de nombreux établissements. Elles ne constituent pas à elles seules cependant, les mesures de prévention primaire visant à limiter à long terme l'impact psychologique de la crise (17,18,36,37). Ces dispositifs se déclinent au niveau de l'institution, de l'encadrement et des soignants, et participent à la reconnaissance du caractère professionnel du stress.…”
Section: Addictionsunclassified
“…Au niveau institutionnel, gestion de crise doit répondre à un certain nombre d'impératifs (18,36) : consignes claires, information actualisée, EPI, tests de dépistage, support logistique (transport, logement, éducation, etc. ), et diffusion de conseils fiables sur la gestion du stress (p.ex., http://cn2r.fr/recommandations-epidemie-covid-19).…”
Section: Soutienunclassified
“…Research has identified that healthcare professionals have requested five things from their employer during the COVID-19 pandemic: hear me, protect me, prepare me, support me, and care for me [20]. For the healthcare workforce to perform to their full potential over an extended time period, healthcare employers must provide early psychosocial support for all employees that addresses these requests and is focused on: creation of a psychologically safe environment, strong leadership, clear organisational strategies for staff wellbeing, consistent communication and significant team support.…”
Section: Introductionmentioning
confidence: 99%
“…The severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) pandemic has put the lives of healthcare workers at great risk, as evidenced by the growing numbers of healthcare worker deaths in many nations [1,2]. The threat to healthcare workers from the virus, and the associated fear, has been further exacerbated by a worldwide shortage of personal protective equipment (PPE) [3,4].…”
Section: Introductionmentioning
confidence: 99%